Random walks and organizational mortality. - Levinthal, Daniel A. (Administrative Science Quarterly, 1991)
A random walk model was developed to examine the relationship of organizational age and mortality rates. In a random walk model, decisions have enduring consequences, the random-walk process can reflect both systemic and stochastic changes in organizational capital that may vary across organizations, and there may be nonsystemic changes in organizational capital. The model was applied to data on the timing of the births and deaths of all newspapers in Ireland from 1800 to 1975 and in Argentina from 1800 to 1900. An empirical analysis examined the degree of heterogeneity in these 2 populations of organizations, and a parametric analysis indicated possible sources of this heterogeneity. The results indicate that surviving organizations tend to be organizations that were successful in prior periods and that prior success will buffer them from subsequent selection pressures.